DEVELOPING CROSS-CULTURAL COMPETENCE THROUGH BATIK TRAINING: THE EXPERIENCE OF XU YATING AS A FOREIGN PARTICIPANT IN INDONESIA - Sabita Noor Dzakwarani Arivandi; Najwa Alya Syafira; Danissa Dyah Oktaviani (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2025)
This study explores the experience of Xu Yating, a foreign national from China, in participating in a batik training program in Indonesia. Batik is not only a traditional textile art but also a significant part of Indonesia’s cultural identity. The training program provided an opportunity for foreign participants to learn the craft of batik directly while gaining insights into local cultural values. Using a qualitative approach through observation and interviews, this research reveals how the training process contributed to both technical skill development and intercultural learning. The findings show that batik training can serve as an effective tool for cultural diplomacy, fostering understanding and appreciation of cultural diversity across nations.